Answer :

We have 13x = 9x + 4x


tan 13x = tan(9x + 4x)


We know that



tan 13x(1 – tan 9x tan 4x) = tan 9x + tan 4x


tan 13x – tan 13x tan 9x tan 4x = tan 9x + tan 4x


tan 13x – tan 9x – tan 4x = tan 13x tan 9x tan 4x


Hence proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses